Kulisy erygowania parafii greckokatolickiej w Międzyrzeczu = Behind-the scenes foundation process of the greek-catholic parish in Międzyrzecz - Wanatko, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the mid-1950s, Poland experienced political transformations. The spirit of change led to the formation of Greek-Catholic parishes in the country, which became a topic discussed by the highest hierarchs of the Roman-Catholic Church and the representatives of the Greek-Catholic Church. Those parishes were also going to be set up in the Lubusz Land, one of them being founded in Międzyrzecz.
Keywords: Międzyrzecz; parafia greckokatolicka; Pasławski, Michał (ksiądz); akcja "Wisła"; Ziemia Lubuska; Ukraińskie Towarzystwo Społeczno-Kulturalne; Greek-Catholic parish; the Operation Vistula; Lubusz Land; Ukrainian Social-Cultural Association